Bio-inspired broadband absorbers induced by copper nanostructures on natural leaves - Trung Duc Dao (Nature Portfolio, 2020)
Abstract In this work, two copper-based biometamaterials were engineered using leaves of water cabbage (Pistia stratiotes) and purple bauhinia (Phanera purpurea) as templates. The copper sputtering was implemented to produce a thin copper film on the surface of leaves. The scanning electron microscopy (SEM) images exhibited the root hair-like nanostructure of water cabbage leaf and single comb-like nanostructure of purple bauhinia leaf. In spite of copper coating, the leaf surfaces of water cabbage and purple bauhinia were black and exhibited excellent light absorption at visible and near infrarrred wavelengths. It was estimated that these two types of leaves could absorb roughly 90% of light. Finite-difference time-domain (FDTD) calculations predicted the low reflectance stemming from the leaf nanostructures and copper coating layer. Because of the low cost of copper as a coating metal and simple procedure, this can be a promising method for quick fabrication of a thin copper film on the leaf nanostructure for application in blackbody or as the light absorbers.